Tailoring selective layer structure for high performance nanofiltration membrane fabrication - Yang, Yang (Nanyang Technological University, 2022)
In recent years, fresh water scarcity has been intensified due to population growth and global climate change. Many researches have been devoted to transfer non-tradition sources of water into clean water. Among multiple choices of water treatment processes, membrane based technology is an energy-efficient separation process. However, current RO and NF membranes are still far from ideal in terms of filtration performance. Thus, this research work mainly focuses on the construction of the NF membrane selective layer with enhanced performance applied in water treatment process. In the literature review part, several fabrication methods applied on a porous substrate to provide separation ability are introduced. When the selective layer is successfully fabricated on the substrate, three mathematical models are reviewed to describe the process in different aspects. With the understanding of how the selective layers achieve separation, the optimization methods are summarized based on the above analysis.